Kaizen as a strategy for continuous improvement of education quality in IT schools (Integrated Islam) - Hastuti, Lili; Alif, Khairunnisa Putri; Madhakomala, Madhakomala (ARKA INSTITUTE, 2025)
Improving the quality of education in schools requires a sustainable and participatory strategy. Kaizen, known as a philosophy of continuous improvement in the industrial world, has the potential to be applied in the educational context. This study aims to explore how Kaizen principles can be adapted as a strategy to improve the quality of education in schools. Through a qualitative case study of an Integrated Islamic School that combines science and Islamic values, this study reveals that the implementation of Kaizen principles supported by the 5S concept, collective participation (teachers, students, and parents), effective leadership, regular evaluation, continuous improvement, and collaboration positively influences work culture and enhances the quality of educational services. These outcomes are facilitated through the use of PDCA, Gemba Walk, Kaizen Event, and the Suggestion System. The conclusion of this study suggests that Kaizen can be an effective strategy in creating an adaptive, participatory, and continuous improvement-oriented education system.